A novel tau‐based rhesus monkey model of Alzheimer's pathogenesis. Issue 6 (18th March 2021) - Beckman, Danielle; Chakrabarty, Paramita; Ott, Sean; Dao, Amanda; Zhou, Eric; Janssen, William G.; Donis‐Cox, Kristine; Muller, Scott; Kordower, Jeffrey H.; Morrison, John H.
Abstract: Introduction: Alzheimer's disease (AD) is a devastating condition with no effective treatments, with promising findings in rodents failing to translate into successful therapies for patients. Methods: Targeting the vulnerable entorhinal cortex (ERC), rhesus monkeys received two injections of an adeno‐associated virus expressing a double tau mutation (AAV‐P301L/S320F) in the left hemisphere, and control AAV‐green fluorescent protein in the right ERC. Noninjected aged‐matched monkeys served as additional controls. Results: Within 3 months we observed evidence of misfolded tau propagation, similar to what is hypothesized to occur in humans. Viral delivery of human 4R‐tau also coaptates monkey 3R‐tau via permissive templating. Tau spreading is accompanied by robust neuroinflammatory response driven by TREM2+ microglia, with biomarkers of inflammation and neuronal loss in the cerebrospinal fluid and plasma. Discussion: These results highlight the initial stages of tau seeding and propagation in a primate model, a more powerful translational approach for the development of new therapies for AD.